Rancangan Acak Kelompok (RAK) pada Analisis Pengaruh Pupuk Bokashi Kotoran Ayam terhadap Pertumbuhan dan Produksi Tanaman Bawang Daun - -, Syilfi; Hidayat, Rahmat (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2024)
This research focused on assessing the impact of chicken manure bokashi on the growth and yield of leeks and determining the optimal dosage for maximizing these outcomes. The study took place from June to August 2023 in Lasalepa Village, Lasalepa District, Muna Regency, using a Randomized Block Design (RBD) with a single factor: chicken manure bokashi fertilizer, tested at five different levels. These levels included a control with no bokashi (B0) and four varying doses: 5 tons/ha (0.6 kg/plot, B1), 10 tons/ha (1.2 kg/plot, B2), 15 tons/ha (1.8 kg/plot, B3), and 20 tons/ha (2.4 kg/plot, B4). Each treatment was repeated three times, resulting in a total of 15 experimental units. The parameters measured included plant height, the number of leaves per clump, the number of tillers per clump, and wet weight per clump. Data were analyzed using analysis of variance (ANOVA), and any significant effects were further explored using the Least Significant Difference (LSD) test at a 95% confidence level. The findings indicated that chicken manure bokashi had a highly significant effect on all measured parameters. The highest yield was observed with the application of 20 tons/ha (2.4 kg/plot) of bokashi, which resulted in an average wet weight of 27.49 grams per clump, equivalent to 3.66 tons/ha.